The diagnostic accuracy of fine needle aspiration cytology in leprosy: a clinico-histopathological correlation - Singh, Arjun; Gaur, Rajesh; Ambey, Ravi (International Journal of Research in Medical Sciences, 2017)
Background: Leprosy is a chronic granulomatous condition mainly affects cooler parts of the body; skin, upper respiratory tract, anterior segment of the eye, superficial portion of peripheral nerves and testes. Redley and Joplin have classified it into five types; Tuberculoid (TT), Borderline Tuberculoid (BT), Mid Borderline (BB), Lepromatous Borderlilne (BL) and Lepromatous (LL). FNAC is simple, rapid and cost effective method over the biopsy to diagnose, classify and monitor leprosy in a patient. The present study was undertaken to evaluate and compare FNAC smears findings with histopathological findings and to classify lesions on RJ scale. Methods:This prospective and descriptive study was done in department of pathology in Sri Venkateshwara institute of medical science, pondicherry, India between June 2007 to June 2010. The patients were examined by the investigator with dermatologist later on slit smear was done. FNAC perform and comparison with biopsy and clinical history was done using SPSS software version 16.0. Results:Total 82 cases were included with age from 8 years to 79 years with mean age 38.16. Male to female ratio was 1.0: 0.7. FNAC shows parity 71.42% for tuberculoid and 58.33% for lepromatous leprosy and histopathology shows parity 100% for tuberculoid and 75% for lepromatous leprosy that indicate FNAC is useful usually for polar or stable group than the unstable or borderline cases. Conclusion:FNAC is a quick and safe for early diagnosis and classify cases into paucibacilary and multibacillary. Exact RJ Scale categorization on FNAC should not be used in isolation but FNAC should be supplemented to the histopathological diagnosis.